Analisis Efektivitas Sistem Informasi Akuntansi Penggajian Karyawan Pada PT. Perkebunan Nusantara III Kebun Bandar Selamat - Siti Nur Adillah; Arnida Wahyuni Lubis (Universitas Muhammadiyah Surabaya, 2023)
Abstract This research aims to analyze the effectiveness of the employee payroll accounting information system at PT. Perkebunan Nusantara III Bandar Selamat. This type of research is descriptive research with a qualitative approach. Data collection in research uses observation, interviews and documentation. The research results show that the functions or parts involved in the procedures used in payroll are good, each procedure will be checked for correctness and suitability before proceeding to the next payroll procedure. The documents used are good in supporting payroll at PT. Perkebunan Nusantara III because it already uses a computer-based payroll system.